A human-animal intervention team model in an alternative middle/high school - Wicker, Judith D., author; Morgan, George A., advisor; Foster, Ann, advisor; Deniston, Terry, committee member; Granger, Ben, committee member (Colorado State University. Libraries, 2005)
The therapeutic impact of the human-animal bond with at-risk youth attending two alternative public school secondary campuses was evaluated during school year 2002- 2003. The purpose of this study was to investigate the effects of animal-assisted therapy or AAT in enhancing secondary-aged youth's social, behavioral, and interpersonal skills. Individual or small group AAT approaches were incorporated into the educational plans of 20 students receiving instruction on one campus site with 11 students comprising the control group on another campus. This study utilized a quasi-experimental approach with manipulation of the independent variable (the presence or absence of AAT participation). The eight dependent variables of social skills, aggressive behavior, attitude to school, interpersonal relations, classroom absences, direction following, acceptance of staff feedback, and respectful responses were measured by a standardized behavioral rating instrument, daily attendance reports, and teacher observations. A posttest only, semi-structured interview of participating staff and students was administered to ascertain underlying attitudes toward the use of AAT with at-risk adolescents. A 3 x 2 factorial design with repeated measures on the second factor was employed. Each of the eight dependent variables was measured through pre and posttest data collection. Neither one-way analyses of variance nor independent samples t tests noted significant changes in social skills, aggressive behavior, attitude to school, interpersonal relations, and classroom absences between treatment groups. When individual and small group AAT results were combined, a paired samples t test analysis for social skills proved significant. Only one paired samples t test comparing daily campus observations showed significance. Anecdotally, staff members saw AAT interventions as having a positive impact upon student behavior. Students also responded positively to their AAT experiences. Pet/client interactions during individual sessions appeared to increase student self-confidence. The small group trainers also felt subjects gained some benefit from their participation. Recommendations for future research and practice included larger sample sizes, lengthier treatment sessions, development of more appropriate measurement tools, and incorporating recognized social skills curricula with AAT interventions. There is still a need for continued research in validating animal-assisted therapy via rigorous scientific methods.
Keywords: special education; behavioral sciences; secondary education; behavioral psychology